2019
DOI: 10.3389/fmicb.2019.01735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Fecal Microbiota in European Mouflon (Ovis orientalis musimon) and Blue Sheep (Pseudois nayaur) Living at Low or High Altitudes

Abstract: The gut microbiota is a complex and essential system organ that plays an integrative role in balancing key vital functions in the host. Knowledge of the impact of altitude on the gut microbiota of European mouflon ( Ovis orientalis musimon ) and blue sheep ( Pseudois nayaur ) is currently limited. In this study, we compared the characteristics of gut microbiota in 5 mouflon at low altitude (K group), 4 mouflon at high altitude (L group), 4 blue sheep at low altitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 75 publications
4
31
0
Order By: Relevance
“…In this study, aiming to establish an appropriate feeding method for domestication of the grasscutter, we investigated its fecal microbiota and compared it with those from other herbivorous livestock in Ghana. Similar to the other animals, the relative abundance of Bacteroidales, Clostridiales, Ruminococcaceae, and Lachnospiraceae-which are the major bacteria groups in herbivores [20][21][22][23]-was high in the fecal microbiota of grasscutters. Moreover, two bacteria genera were especially abundant in the fecal microbiome of grasscutters, Prevotella and Treponema, whose levels were higher in grasscutters than those in any other animal.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, aiming to establish an appropriate feeding method for domestication of the grasscutter, we investigated its fecal microbiota and compared it with those from other herbivorous livestock in Ghana. Similar to the other animals, the relative abundance of Bacteroidales, Clostridiales, Ruminococcaceae, and Lachnospiraceae-which are the major bacteria groups in herbivores [20][21][22][23]-was high in the fecal microbiota of grasscutters. Moreover, two bacteria genera were especially abundant in the fecal microbiome of grasscutters, Prevotella and Treponema, whose levels were higher in grasscutters than those in any other animal.…”
Section: Discussionmentioning
confidence: 81%
“…The influence of high-altitude can impose thermoregulatory challenges on wild animals, and these stressors may affect both survival and reproduction [ 65 , 66 ]. In this study, dimensionality reduction and correlation analysis results revealed several functional genes enhance as the altitude increased, especially functional groups related to metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the environment dominates host genetics in shaping the human gut microbiota (Rothschild et al, 2018). A higher F/B ratio might help hosts effectively harvest energy from their diet to maintain energy homeostasis and core body temperature in harsh environments (Sun et al, 2019; Zhao et al, 2018). However, the adaptive mechanism by which the gut microbiota mediates energy absorption is much more complex and warrants further investigation in this unique living environment.…”
Section: Altitudinal Variation In the Gut Microbiotamentioning
confidence: 99%